Trends in condom use among female sex workers in Andhra Pradesh, India: the impact of a community mobilisation intervention. - Erausquin, Jennifer Toller; Biradavolu, Monica; Reed, Elizabeth; Burroway, Rebekah; Blankenship, Kim M (Journal of epidemiology and community health, 2012)
Community mobilisation interventions for HIV prevention among female sex workers (FSWs) aim to organise FSWs for collective action and challenge the structures of power that underlie HIV risk. Assessing intervention impact is challenging because the importance of direct individual exposure to intervention components may decrease over time as change occurs at social-normative, policy and other structural levels. In this paper, the authors examine changes over time in consistent condom use among FSWs in Rajahmundry, Andhra Pradesh, the location of a long-standing community mobilisation intervention.
Keywords: Adolescent; Adult; Community Networks; Condoms; Cross-Sectional Studies; Female; Health Knowledge, Attitudes, Practice; Health Promotion; HIV Infections; Humans; India; Logistic Models; Program Evaluation; Prostitution; Risk Reduction Behavior; Safe Sex; Sex Workers; Socioeconomic Factors; Time Factors; Young Adult